2010
DOI: 10.3176/proc.2010.3.05
|View full text |Cite
|
Sign up to set email alerts
|

Structure and curing mechanism of resol phenol-formaldehyde prepolymer resins

Abstract: Prepolymer resol resins with different phenol/formaldehyde/NaOH molar ratios were synthesized and characterized by technical analysis as well as by 13 C NMR spectra for samples in CD 3 OD solution. Larger amounts of NaOH promoted the binding of formaldehyde and para substitution including the formation of benzoquinone rings with two o, p′-methylene groups in the para position. The polycondensation between ortho-hydroxymethyl groups and one-substituted aromatic para positions as the main thermosetting curing pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“… provided evidence that these intermediates do exist in UF reaction mixtures. Literature is ambiguous on whether the formation of these components is favored under basic conditions during hydroxymethylation or under neutral to acidic conditions during condensation and curing. In this work, methoxymethylene bridges were not taken into account.…”
Section: Chemical Reaction Systemmentioning
confidence: 99%
“… provided evidence that these intermediates do exist in UF reaction mixtures. Literature is ambiguous on whether the formation of these components is favored under basic conditions during hydroxymethylation or under neutral to acidic conditions during condensation and curing. In this work, methoxymethylene bridges were not taken into account.…”
Section: Chemical Reaction Systemmentioning
confidence: 99%
“…It is found that the compositions of phenol formaldehyde resins changed with the varying catalyst to phenol molar ratio, formaldehyde to phenol molar ratio, reaction temperature and pH [18,19] , we researched a series of PF resin synthesized with different synthesize conditions to identify suitable synthetic resin technology.…”
Section: Results and Discussion Materials Mixture Ratios Effect On Curmentioning
confidence: 99%
“…This result was confirmed by previously published results. 8,30,31 The peak at 154-157 ppm is attributed to uron-type structures, because the carbonyl resonance is shifted toward a higher field in comparison to noncyclic components. The small value of uron ring structures observed just in the HCOOH-catalyzed (1.66, Table II) and HCl-catalyzed cases (0.13, Table II) is due to the fact that uron structures are generally in a very minor proportion when the F/U molar ratio is around 2.1.…”
Section: C-nmr Spectramentioning
confidence: 99%